2022
DOI: 10.3389/fphar.2022.811030
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Data Mining Approach Reveal the Medication Rule of Traditional Chinese Medicine in the Treatment of Premenstrual Syndrome/Premenstrual Dysphoric Disorder

Abstract: Premenstrual syndrome (PMS) is a common disorder that affects women of reproductive age. It is characterized by periodic mental and somatic symptoms such as irritability, depression, and breast pain during the luteal phase. Premenstrual dysphoric disorder (PMDD) is the most severe form of PMS. In recent years, the incidence of PMS/PMDD has been increasing year after year. However, due to the complex symptoms and ambiguous classification of PMS/PMDD, the limitations of present treatments, such as their poor eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Sun et al [27] revealed the mechanisms of TCM in the treatment of Mycoplasma pneumoniae pneumonia based on data mining and systematic pharmacology. Qu et al [28] revealed the medication rule of TCM in the treatment of premenstrual syndrome/premenstrual dysphoric disorder through network pharmacology and data mining approach.…”
Section: Related Workmentioning
confidence: 99%
“…Sun et al [27] revealed the mechanisms of TCM in the treatment of Mycoplasma pneumoniae pneumonia based on data mining and systematic pharmacology. Qu et al [28] revealed the medication rule of TCM in the treatment of premenstrual syndrome/premenstrual dysphoric disorder through network pharmacology and data mining approach.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, further research into the neural circuits and neural endocrine mechanisms of MDD and PMDD as well as treatment moving toward translational medicine and drug development are keys to solving the above problems. Meta-analysis and animal experimental evidence have shown the high potential of complementary and alternative therapies in the treatment of PMDD and MDD ( 21 , 22 ). Unlike single-target chemical drugs, Chinese medicine therapy can regulate specific neural circuits and neuroendocrine functions with multiple targets and pathways to treat these diseases, avoiding the side effects of chemotherapy and representing a promising therapeutic direction.…”
mentioning
confidence: 99%